Efek Likuefaksi Nickel Ore pada Stabilitas dan Olah Gerak Kapal MV. Nur Allya - Fanny Darwani Putri (Applied Science and Technology on Naval Engineering, 2024)
Nickel ore liquefaction can cause the vessel to tip and sink in a short time due to the change in shape of the charge from solid to liquid. As a result, when the ship experienced a large shock, the cargo could not return to its original position. The purpose of this study is to determine the percentage composition between nickel in solid and liquid form with a total of 100% in the load chamber. The method used in this study was to analyze the effect of nickel ore fluidity on the stability and motion of MV ships. Nur Allya. The stability results of the ship are carried out in five cases, namely: 100% solid, 75% solid 25% liquid, 50% solid 50% liquid, 25% solid 75% liquid, and 100% liquid. The best result was obtained in case 1 with a maximum GZ value = 1.064 m. To prevent this incident, the study added a longitudinal bulkhead to the load chamber in all five cases. The results show a small increase in the increment in case 1 compared to case 5. Although the longitudinal bulkhead reduces the risk of liquefaction, the ship's cargo capacity is reduced. After that, an analysis of the movement of the ship was carried out such as: roll, pitch, and heave, showing the difference in response to the condition of the direction of the following sea, beam sea, and head sea waves. The biggest response occurred in the sea beam so that the seakeeping quality of the ship was getting worse. In this case, because the ship cannot dampen the exposure of the waves that hit the ship's body.